2011
DOI: 10.1039/c0jm03846f
|View full text |Cite
|
Sign up to set email alerts
|

The selective immobilization of curcumin onto the internal surface of mesoporous hollow silica particles by covalent bonding and its controlled release

Abstract: Mesoporous-type spherical hollow silica nanoparticles were prepared by using a self-assembled alanine-based amphiphile as a template and then were functionalized with curcumin molecules attached to the internal surface of the nanostructure by covalent bonding. The curcumin-immobilized mesoporous hollow silica nanoparticle (C-MHSP) was characterized by transmission electron microscopy (TEM), scanning electron microscopy (SEM), BET isotherms, FT-IR, Solid 13 C CP/MAS NMR and powder-XRD. SEM and TEM images reveal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 41 publications
0
27
0
Order By: Relevance
“…On the other hand, covalent bonding could also be used to construct controlled drug release systems. Jin et al proved that curcumin molecules, which were selectively attached to the inside surface of HMSNs by covalent bonding, could be effectively released by the cleavage of the amide bond by the selected base . Thus, it is believed that this system, based on the amide bond, would be very promising for fabricating custom‐made controlled‐delivery devices triggered by specific target molecules.…”
Section: Functionalization and Applications Of Hmmsmentioning
confidence: 99%
“…On the other hand, covalent bonding could also be used to construct controlled drug release systems. Jin et al proved that curcumin molecules, which were selectively attached to the inside surface of HMSNs by covalent bonding, could be effectively released by the cleavage of the amide bond by the selected base . Thus, it is believed that this system, based on the amide bond, would be very promising for fabricating custom‐made controlled‐delivery devices triggered by specific target molecules.…”
Section: Functionalization and Applications Of Hmmsmentioning
confidence: 99%
“…36,37 Despite Cur’s remarkable anticancer characteristics, its extremely low water solubility and poor bioavailability are impeding its wide clinical use. To address this issue, in previous studies, Cur has been loaded into various inert carriers such as mesoporous silica nanoparticles, 38,39 gold nanoparticles 40 and polymeric nanoparticles. 41,42 However, in addition to their low Cur-loading capacities, the large amounts of inert carriers used could lead to other concerns, including their metabolism and potential long-term toxicity.…”
Section: Introductionmentioning
confidence: 99%
“…As curcumin is a promising pro-drug, a few studies have been reported recently on curcumin delivery based on MSNs. Their aim was to enhance the cytotoxicity of curcumin and exploit the effect of surface functionality on cellular uptake and anticancer activity when utilizing the MCM-41 type [35,36], as well as curcumin-loaded guanidine for combating breast cancer using KIT-6 silica type [37] and controlled release of curcumin from hollow silica material [38,39]. However, to the best of our knowledge no reports on utilization of KCC-1 silica type in delivery of curcumin as model anticancer natural pro-drugs yet reported, and also no comparative study to analyze the differences between the KCC-1 material and commonly used MCM-41 type in controlled release of the small molecule drugs has been carried out.…”
Section: Introductionmentioning
confidence: 99%